2023
DOI: 10.3390/ph16030386
|View full text |Cite
|
Sign up to set email alerts
|

Saponins of Selected Triterpenoids as Potential Therapeutic Agents: A Review

Abstract: Saponins represent important natural derivatives of plant triterpenoids that are secondary plant metabolites. Saponins, also named glycoconjugates, are available both as natural and synthetic products. This review is focused on saponins of the oleanane, ursane, and lupane types of triterpenoids that include several plant triterpenoids displaying various important pharmacological effects. Additional convenient structural modifications of naturally-occurring plant products often result in enhancing the pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Phenolics exhibit a range of bioactivities, including antimicrobial, anticancer, and antioxidant effects [ 93 ]. Pisolactone and 7,22-dien-3-ol, 24-methyl lanostane are two triterpenoids, and this class of organic compounds has been described as potential antimicrobial and anticancer drugs [ 94 , 95 ]. Pisosterol is a triterpene.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics exhibit a range of bioactivities, including antimicrobial, anticancer, and antioxidant effects [ 93 ]. Pisolactone and 7,22-dien-3-ol, 24-methyl lanostane are two triterpenoids, and this class of organic compounds has been described as potential antimicrobial and anticancer drugs [ 94 , 95 ]. Pisosterol is a triterpene.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the oleanane-type skeleton is a classical pentacyclic skeleton and commonly exists in many families, such as Araliaceae [ 24 ], Fabaceae [ 25 ], Campanulaceae [ 26 ], Polygalaceae [ 27 ], etc. In the previous phytochemical investigation of the Primulaceae family, it was found that oleanane-type skeletons, especially 13,28-epoxyoleanane skeletons, were the general feature of the main components of this family [ 28 ]. As a genus from the Primulaceae family, many oleanane-type triterpenoid saponins, more than half of which having beard 13,28-epoxyoleanane skeletons, have been isolated from the Lysimachia genus [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…One such compound is saponin, a bioactive component found in various plants ( 28 ). Saponin possesses multiple pharmacological properties, including anti-inflammatory, anti-fibrotic, antioxidant and anticancer effects ( 29 , 30 ). The anticancer potential of saponins have been demonstrated in various types of cancers, including breast, gastric and colorectal cancers ( 31 ).…”
Section: Discussionmentioning
confidence: 99%